2003
DOI: 10.1111/1467-8306.9303003
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Perspectives on Air Pollution and Environmental Justice in Hamilton, Canada, 1985–1996

Abstract: This article addresses two questions: (1) How do spatiotemporal changes in air pollution levels-specifically, total suspended particulates (TSP)-rise or fall with socioeconomic status? (2) A critical equity interpretation of environmental policy then motivates this question: does the pursuit of average regional reductions in pollution benefit those who need improvements least, benefit those who need improvements most, or maintain the status quo? TSP data are drawn from networks of monitoring stations operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 57 publications
0
70
0
Order By: Relevance
“…Past studies in Hamilton have shown a negative relationship between socio-economic status and exposure to air pollution (Jerrett et al, 2001;Buzzelli et al, 2003;Buzzelli & Jerrett, 2004). Some evidence suggests that certain visible minority groups may also be disproportionately exposed (Buzzelli & Jerrett, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies in Hamilton have shown a negative relationship between socio-economic status and exposure to air pollution (Jerrett et al, 2001;Buzzelli et al, 2003;Buzzelli & Jerrett, 2004). Some evidence suggests that certain visible minority groups may also be disproportionately exposed (Buzzelli & Jerrett, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…15,16 These findings have served to mobilize a new form of environmental activism, organized around the pursuit of environmental justice. This movement, particularly in the United States, has emphasized the fight against environmental racism-that is, policies and practices that place facilities and pollution more frequently in the vicinity of people of color.…”
Section: Linking Health Inequality and Environmental Justicementioning
confidence: 99%
“…Disadvantaged communities are defined by common markers of social disparities including income (Evans and Kantrowitz 2002), ethnicity and race (Bhat 2005;Green et al 2004;Morello-Frosch and Jesdale 2006;Apelberg et al 2005;Mirabelli et al 2006), employment (Cummins et al 2005), education (Buzzelli et al 2006) and family status (Buzzelli et al 2003). Studies of environmental justice are inherently spatial in nature (Sheppard et al 1999) requiring the selection of an appropriate spatial methodology for analyzing the relationship between population and environmental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of each SES variable with NO 2 was investigated first and variables were kept if they took the hypothesized/expected sign in both correlation and OLS models. To test the efficacy of the prediction models, we evaluated whether selected variables were collinear based on variance inflation factors (VIFs) and whether the model results had spatial autocorrelation (Buzzelli et al 2003). If the models display spatial autocorrelation, least squares estimators may be biased and inconsistent; an aspect of spatial data that ought to be addressed in multivariate regression (Getis 1990).…”
Section: Introductionmentioning
confidence: 99%